New oral anticoagulants in thrombotic antiphospholipid syndrome. (October 2014) - Chighizola, CB; Moia, M; Meroni, PL
A main goal in clinical management of patients with antiphospholipid syndrome (APS) is to prevent thrombotic recurrences and/or miscarriages. For many decades, the only available oral anticoagulant drugs have been vitamin K antagonists (VKA), which are still the cornerstone of long-term treatment of thromboembolism. However, the limits of VKA treatment are well known: narrow therapeutic window and high patient-to-patient variability of response. Moreover, in some patients with APS a higher international normalized ratio (INR) therapeutic target was suggested, and INR inaccuracy due to antiphospholipid antibodies was reported. Therefore, VKA management in APS patients is frequently cumbersome, requires close INR monitoring and may affect patient's quality of life. A new class of oral anticoagulant agents has been developed, the Direct Oral Anticoagulants (DOA), which directly inhibit a single enzyme of the coagulation cascade. Compared with VKA, they have more stable pharmacokinetic and pharmacodynamic profiles, little interaction with food or drugs with a predictable anticoagulation effect, they can thus be prescribed in a fixed dose, without requiring frequent laboratory monitoring. The efficacy and safety of DOA has been shown in large phase III clinical trials. Unfortunately, translating these good results to APS patients is not straightforward: currently, at least three randomized controlled clinical trials are ongoing.